L’archeologia a volo d’uccello: un Report dal Secondo Convegno di Archeologia Aerea - Carlucci, valerio (Archeomatica, 2016)
At the Belgica Academy of Rome was held the 2nd International Congress of Aerial Archaeology "From balloons to the drones: aerial images in Archaeology", promoted by the University of Salento in collaboration with the University of Ghent and the University of Cassino and Southern Lazio.